Electrochemical wettability control on conductive TiO2 nanotube surfaces modified with a ferrocene redox system - Schmidt-Stein, F.; Gnichwitz, Jan-Frederik; Salonen, J.; Hahn, Robert; Hirsch, Andreas; Schmuki, Patrik (Electrochemistry Communications, 2009)
This work reports on an electrochemical system which allows the control of surface wettability properties by voltage induced changes in contact angle (Θ) of ΔΘ ≥ 50°. For this we used conductive TiO nanotubular layers that were modified with ferrocene coupled to the TiO surface via triethoxysilane. To enhance the hydrophobic character of the nanotubular TiO surface, also mixed organic monolayers namely perfluorotriethoxysilane, were explored. Formation of the ferrocene and mixed organic monolayer was confirmed by X-ray-photoelectron-spectroscopy (XPS). Contact angle combined with electrochemical measurements show that ferrocene in these monolayers can successfully be switched from Fe to Fe and that this change in the redox state considerably alters the wetting properties. Using a conductive nanotube substrate allows us to amplify this change by a factor of more than 10, and thus this surface can be used to trigger significant wetting alterations. © 2009 Elsevier B.V. All rights reserved.

Fast formation of aligned high-aspect ratio TiO2 nanotube bundles that lead to increased open circuit voltage when used in dye sensitized solar cells - Jha, Himendra; Roy, Poulomi; Hahn, Robert; Paramasivam, Indhumati; Schmuki, Patrik (Electrochemistry Communications, 2011)
Ultrafast formation of high-aspect ratio titanium dioxide nanotube is carried out by the rapid-breakdown-anodizing technique using a two compartment electrochemical cell. The change in surface morphology of the titanium substrate during anodization, and physical parameters such as pH and temperature are investigated. Under optimized conditions, aligned TiO2 nanotube powder is obtained that beneficially can be used in dye-sensitized solar cells. Solar cell constructed using the nanotube powder can show a significantly higher open circuit voltage than when constructed with commercially available nanoparticles.
EAM Import::2019-03-14

Formation of aligned nanoporous/nanotubular layers of vanadium oxy-nitrides - Yang, Yang; Kirchgeorg, Robin; Hahn, Robert; Schmuki, Patrik (Electrochemistry Communications, 2014)
Self-organized vanadium oxy-fluoride nanotubular or nanoporous layers were grown by anodization of vanadium in a [BF4]- electrolyte. By a thermal conversion of this amorphous VOxFy precursor structure in ammonia gas, aligned vanadium oxy-nitride (VOxNy) nanoporous/nanotubular layers could be formed. We established conditions to reach conversion of precursor structures to a well crystallized VOxNy nanotube structure, without the formation of any secondary phases or the collapse of the ordered morphology. Such vanadium-nitride based structures have considerable potential in supercapacitor applications.
EAM Import::2019-03-14

Formation of Self-Organized Superlattice Nanotube Arrays - Embedding Heterojunctions into Nanotube Walls - Wei, Wei; Jha, Himendra; Yang, Guang; Hahn, Robert; Paramasivam, Indhumati; Berger, Steffen; Spiecker, Erdmann; Schmuki, Patrik (Advanced Materials, 2010)
In the present work we introduce the growth of 3D-superlattice nanotubes by a simple anodization technique. Highly defined self-organized, oxide tubes with modulated tube wall composition can be created that allow altering and tuning optical, electrical, and chemical properties of such nanometer-size architectures. The image shows a stacked nanotube array with built-in TiO2/Ta-2 O-5 heterojunctions.

Interface Chemistry and Molecular Bonding of Functional Ethoxysilane-Based Self-Assembled Monolayers on Magnesium Surfaces - Killian, Manuela; Seiler, Steffen; Wagener, Victoria; Hahn, Robert; Ebensperger, Christina; Meyer, Bernd; Schmuki, Patrik (ACS Applied Materials and Interfaces, 2015)
The modification of magnesium implants with functional organic molecules is important for increasing the biological acceptance and for reducing the corrosion rate of the implant. In this work, we evaluated by a combined experimental and theoretical approach the adsorption strength and geometry of a functional self-assembled monolayer (SAM) of hydrolyzed (3-aminopropyl)triethoxysilane (APTES) molecules on a model magnesium implant surface. In time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS), only a minor amount of reverse attachment was observed. Substrate–O–Si signals could be detected, as well as other characteristic APTES fragments. The stability of the SAM upon heating in UHV was investigated additionally. Density-functional theory (DFT) calculations were used to explore the preferred binding mode and the most favorable binding configuration of the hydrolyzed APTES molecules on the hydroxylated magnesium substrate. Attachment of the molecules via hydrogen bonding or covalent bond formation via single or multiple condensation reactions were considered. The impact of the experimental conditions and the water concentration in the solvent on the thermodynamic stability of possible APTES binding modes is analyzed as a function of the water chemical potential of the environment. Finally, the influence of van der Waals contributions to the adsorption energy will be discussed.
Keywords: DFT calculations; magnesium; self-assembled monolayer; silane coupling; ToF-SIMS

Intrinsic Au Decoration of Growing TiO2 Nanotubes and Formation of a High-Efficiency Photocatalyst for H2 Production - Lee, Kiyoung; Hahn, Robert; Altomare, Marco; Selli, Elena; Schmuki, Patrik (Advanced Materials, 2013)
Electrochemical anodization of low-concentration (0.02–0.2 at% Au) TiAu alloys in a fluoride electrolyte leads to self-organized TiO2 nanotubes that show a controllable, regular in situ decoration with elemental Au nanoclusters of ≈5 nm in diameter. The degree of self-decoration can be adjusted by the Au concentration in the alloy and the anodization time. Such Au particle decorated tubes show a high activity for photocatalytic H2 production from ethanol solutions.
EAM Import::2019-03-13

Key factors for an improved lithium ion storage capacity of anodic TiO2 nanotubes - Kirchgeorg, Robin; Kallert, Max; Liu, Ning; Hahn, Robert; Killian, Manuela; Schmuki, Patrik (Electrochimica Acta, 2016)
In the present work we investigate key factors that influence the Li-storage capacity of anodically grown self-organized TiO2 nanotube layers. First, the influence of both tube length and top morphology are investigated regarding the rate performance of the nanotube layers. Then, factors such as the presence of initiation (grass) layers and the influence of the double walled morphology of conventional TiO2 nanotube layers are elaborated. At high C-rates a grass layer even shows a beneficial contribution, mainly by adding to the double layer capacitance. The presence of a double wall morphology and the associated carbon contamination lead to a lower intercalation ability. Two different approaches are taken to eliminate the inner carbon-rich layer: Cathodic polarization and tube formation in DMSO based electrolytes. This results in an enhancement of the areal capacity by 17% and 33% compared to unmodified tube layers for the two approaches.
EAM Import::2019-03-12

Magnetically Guided Titania Nanotubes for Site-Selective Photocatalysis and Drug Release - Shrestha, Nabeen Kumar; Macák, Jan; Schmidt-Stein, F.; Hahn, Robert; Mierke, Claudia; Fabry, Ben; Schmuki, Patrik (Angewandte Chemie, 2008)
Quick release: The spatial and temporal delivery of active molecules (dyes or drugs) can be precisely controlled by the photocatalytic activity of TiO_2 nanotubes (see picture). The cleavage of the link between the active molecule and the nanotubes, which are filled with magnetic Fe_3O_4 nanoparticles, occurs by photoinduced chain scission under UV light; the load can be released before photodegradation by action of photogenerated radicals can occur.

NH3 treatment of TiO2 nanotubes: from N-doping to semimetallic conductivity - Al-Thabaiti, Shaeel A.; Hahn, Robert; Liu, Ning; Kirchgeorg, Robin; So, Seulgi; Schmuki, Patrik; Basahel, Sulaiman N.; Bawaked, Salem M. (Chemical Communications, 2014)
In the present work we show that a suitable high temperature ammonia treatment allows for the conversion of single-walled TiO2 nanotube arrays not only to a N-doped photoactive anatase material (which is already well established), but even further into fully functional titanium nitride (TiN) tubular structures that exhibit semimetallic conductivity.
EAM Import::2019-03-12

Nickel Hydroxide Nanoparticle Activated Semi-metallic TiO2 Nanotube Arrays for Non-enzymatic Glucose Sensing - Gao, Zhi-Da; Guo, Jing; Shrestha, Nabeen Kumar; Hahn, Robert; Song, Yan-Yan; Schmuki, Patrik (Chemistry - A European Journal, 2013)
Semi-metallic TiO2 nanotube arrays (TiOxCy NTs) have been decorated uniformly with Ni(OH)2 nanoparticles without the aid of a polymer binder. The resulting hybrid nanotube arrays exhibit excellent catalytic activity towards non-enzymatic glucose electro-oxidation. The anodic current density of the glucose oxidation is significantly improved compared with traditional TiO2 nanotubes decorated with Ni(OH)2. Moreover, the Ni(OH)2/TiOxCy NT-based electrode shows a fast response, high sensitivity, wide linear range, good selectivity and stability towards glucose electro-oxidation, and thus provides a promising and cost-effective sensing platform for non-enzymatic glucose detection.
EAM Import::2019-03-08

Open top anodic Ta3N5 nanotubes for higher solar water splitting efficiency - Grigorescu, Sabina Georgiana; So, Seulgi; Yoo, Jeong Eun; Mazare, Anca Valentina; Hahn, Robert; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work we grow self-organized Ta2O5 nanotube layers in a H2SO4/NH4F electrolyte at various elevated temperatures. Under optimized conditions we obtain 4 extgreekmm long nanotubes that are well adherent to the substrate and can be grown very homogenous over large surface areas. Moreover, the key advantage of this approach is that an open top morphology (initiation layer free) is obtained. After a suitable conversion treatment in NH3 atmosphere Ta3N5 nanotubes are obtained, that after (Co-Pi+Co(OH)x) modification provide, under AM 1.5G illumination conditions, a photoelectrochemical current response of 4.7 mA cm-2 at +1.23 V vs RHE.
EAM Import::2019-03-08

Ordered nanotubular titanium disulfide (TiS2) structures: Synthesis and use as counter electrodes in dye sensitized solar cells (DSSCs) - Licklederer, Markus; Cha, Gi; Hahn, Robert; Schmuki, Patrik (Journal of The Electrochemical Society, 2019)
TiS2 nanotubular structures were synthesized by a high temperature H2S treatment of anodized TiO2 nanotube layers, and their electrochemical activity for a use as counter electrodes in dye sensitized solar cells (DSSCs) was evaluated. During conversion to TiS2 compositional, morphological and structural transformations were monitored. The fully converted TiS2 nanostructures show a high electrocatalytic activity for the I-/I3-oxidation comparable to a nanoparticular platinum layer. For a simplified model a DSSC solar cell efficiency of 6.1% was obtained using the TiS2 nanotube layer as counter electrode, which is very close to values obtained for a Pt reference (6.2%).
CRIS-Team Scopus Importer:2020-02-21

Oxide Nanotubes on Ti-Ru Alloys: Strongly Enhanced and Stable Photoelectrochemical Activity for Water Splitting - Roy, Poulomi; Das, Chittaranjan; Lee, Kiyoung; Hahn, Robert; Ruff, Tobias; Moll, Matthias; Schmuki, Patrik (Journal of the American Chemical Society, 2011)
The present work shows a significant enhancement of the photoelectrochemical water-splitting performance of anodic TiO2 nanotube layers grown on low concentration (0.01-0.2 at% Ru) Ti-Ru alloys. Under optimized preparation conditions (0.05 at% Ru, 450 °C annealing) the water splitting rate of the oxide tubes could be 6-fold increased. Moreover, the beneficial effect is very stable with illumination time; this is in contrast to other typical doping approaches of TiO2.
EAM Import::2019-03-08

Palladium Activated Decoration of TiO2 Nanotubes by Copper Nanoparticles and Enhanced Photocatalytic Properties - Liu, Ning; Jha, Himendra; Hahn, Robert; Schmuki, Patrik (ECS Electrochemistry Letters, 2012)
The present work describes how a simple two step activation/deposition process can be used to uniformly decorate TiO2 nanotube layers with suitable nanoparticles. In a first step Pd-activation is used to create initiation sites for a subsequent chemical deposition, in our example, Cu. We show that the procedure for two different nanotube types, when optimized, can yield very homogeneous particle decoration of the tube walls down to the bottom of the nanotubes. In the present case deposition and air exposure lead to mixed Cu/Cu-oxide decoration. We illustrate that this combination can be used for effective visible light photocatalysis.
EAM Import::2019-03-08

Photocatalytic H2 production on self-decorated Au nanoparticles/TiO2 nanotubes under visible light - Lee, Kiyoung; Hahn, Robert; Schmuki, Patrik (Electrochemistry Communications, 2014)
In the present work we fabricate TiO2 nanotubes that are self-decorated with Au nanoparticles by anodizing low concentration (0.02 and 0.2 at.% Au) TiAu alloys. After formation, the TiO2 tube walls carry regularly dispersed self-decorated Au particles with 5 nm in diameter which cause significant surface plasmon resonances. This plasmon resonance effect can be exploited to achieve visible photoresponse and can be used for photocatalytic H2 production under visible light illumination.
EAM Import::2019-03-12

Photocatalytic properties of in situ doped TiO2-nanotubes grown by rapid breakdown anodization - Hahn, Robert; Stark, Martin; Killian, Manuela; Schmuki, Patrik (Catalysis: Science and Technology, 2013)
In the present work, we demonstrate an in situ electrochemical doping approach during the growth of TiO2 nanotubular layers formed by rapid breakdown anodization (RBA). For this, several oxygen containing metal anions, as doping species (WO42-, Al(OH)4-, SiO32-, MoO42-, SnO44-, CrO42- and MnO4-), were investigated as additives to the electrolyte and successfully incorporated into the nanotubular oxide during the ultrafast tube growth. A linear relationship between the concentration of anions in the electrolyte and the doping concentration in the oxide was found. The resulting doped layers were tested, after heat treatment, for their UV photocatalytic activity using the degradation of AO7 (an organic model compound routinely used for determining the kinetics of photocatalytic decomposition reactions).
EAM Import::2019-03-12

Self-decoration of Pt metal particles on TiO2 nanotubes used for highly efficient photocatalytic H2 production - Basahel, Sulaiman N.; Lee, Kiyoung; Hahn, Robert; Schmuki, Patrik; Bawaked, Salem M.; Al-Thabaiti, Shaeel A. (Chemical Communications, 2014)
Pt decorated TiO2 has, over the past decades, been a key material for photocatalytic hydrogen production. The present work shows that growing anodic self-organized TiO2 nanotubes from Ti-Pt alloy with a low Pt content of 0.2 at% leads to oxide nanotube layers that are self-decorated with Pt nanoparticles of 4-5 nm in diameter. The average particle spacing is in the range of 50 nm and is partially adjustable by the anodization conditions. This intrinsic decoration of TiO2 nanotubes with Pt leads to a highly active photocatalyst for the production of H2 under UV or visible light conditions.
EAM Import::2019-03-13

Semimetallic TiO2 Nanotubes - Hahn, Robert; Schmidt-Stein, Felix; Salonen, Jarno; Thiemann, Stefan; Song, Yanyan; Kunze, Julia; Lehto, Vesa-Pekka; Schmuki, Patrik (Angewandte Chemie International Edition, 2009)
Orchestrating conductors: A carbo-thermal reduction treatment of a TiO_2 nanotube layer in acetylene converts the tube walls into highly conductive and stable oxy carbide compounds. The resulting semimetallic TiO_2 nanotube layers (TiOxCy) are electrode materials with properties that differ from other TiO_2 nanotubes (see picture). They have a high oxygen overpotential and can be used as a catalyst support, for example, for methanol oxidation.
EAM Import::2019-03-13

Tungsten doping of Ta3N5-nanotubes for band gap narrowing and enhanced photoelectrochemical water splitting efficiency - Grigorescu, Sabina Georgiana; Bärhausen, Benedikt; Wang, Lei; Mazare, Anca Valentina; Yoo, Jeong Eun; Hahn, Robert; Schmuki, Patrik (Electrochemistry Communications, 2015)
Ordered W-doped Ta2O5 nanotube arrays were grown by self-organizing electrochemical anodization of TaW alloys with different tungsten concentrations and by a suitable high temperature ammonia treatment, fully converted to W:Ta3N5 tubular structures. A main effect found is that W doping can decrease the band gap from 2 eV (bare Ta3N5) down to 1.75 eV. Ta3N5 nanotubes grown on 0.5 at.% W alloy and modified with Co(OH)x as co-catalyst show 33% higher photocurrents in photoelectrochemical (PEC) water splitting than pure Ta3N5.
EAM Import::2019-03-13

Visible light photo response from N-doped anodic niobium oxide after annealing in ammonia atmosphere - Ruff, T.; Hahn, Robert; Killian, M. S.; Asoh, H.; Ono, S.; Schmuki, Patrik (Electrochimica Acta, 2012)
Niobium oxide films with a thickness of approximately 165 nm were prepared by electrochemical anodization. These anodic oxide layers were then treated in an ammonia atmosphere at different temperatures and durations, and characterized with XRD, XPS, ToF-SIMS and photoelectrochemical methods. Under optimized conditions nitrogen doping of the niobium oxide films takes place, resulting in a distinct photo response in the visible range of light.
EAM Import::2019-03-13

X-ray induced photocatalysis on TiO2 and TiO2 nanotubes: Degradation of organics and drug release - Schmidt-Stein, F.; Gnichwitz, Jan-Frederik; Salonen, J.; Hahn, Robert; Hirsch, Andreas; Schmuki, Patrik; et al. (Electrochemistry Communications, 2009)
The photocatalytic activity of titanium dioxide under X-ray radiation is of great interest for biomedical applications. In the present work we explore the use of compact TiO layers and TiO nanotubes for X-ray induced photocatalysis, in particular the degradation of organics and monolayer chain scission for drug release. The radiation was done with a conventional X-ray source and doses up to 50 × 10 J/kg. The results show the feasibility of X-ray catalysis on TiO and X-ray induced monolayer chain scission by the release of surface attached Zn-porphyrin molecules. Furthermore, a higher efficiency for anatase films and nanotubes is obtained than for amorphous morphologies. © 2009 Elsevier B.V. All rights reserved.